Early experience of thoracoscopic vs. catheter ablation for atrial fibrillation. Issue 5 (6th February 2019) - Pearman, Charles M; Redfern, James; Williams, Emmanuel A; Snowdon, Richard L; Modi, Paul; Hall, Mark C S; Modi, Simon; Waktare, Johan E P; Mahida, Saagar; Todd, Derick M; Mediratta, Neeraj; Gupta, Dhiraj
Abstract: Aims: Video-assisted thoracoscopic surgery (VATS) ablation has been advocated as a treatment option for non-paroxysmal atrial fibrillation (AF) in recent guidelines. Real-life data on its safety and efficacy during a centre's early experience are sparse. Methods and results: Thirty patients (28 persistent/longstanding persistent AF) underwent standalone VATS ablation for AF by an experienced thoracoscopic surgeon, with the first 20 cases proctored by external surgeons. Procedural and follow-up outcomes were collected prospectively, and compared with 90 propensity-matched patients undergoing contemporaneous catheter ablation (CA). Six (20.0%) patients undergoing VATS ablation experienced ≥1 major complication (death n  = 1, stroke n  = 2, conversion to sternotomy n  = 3, and phrenic nerve injury n  = 2). This was significantly higher than the 1.1% major complication rate (tamponade requiring drainage n  = 1) seen with CA ( P  < 0.001). Twelve-month single procedure arrhythmia-free survival rates without antiarrhythmic drugs were 56% in the VATS and 57% in the CA cohorts ( P  = 0.22), and 78% and 80%, respectively given an additional CA and antiarrhythmic drugs ( P  = 0.32). Conclusion: During a centre's early experience, VATS ablation may have similar success rates to those from an established CA service, but carry a greater risk of major complications. Those embarking on a programme of VATS AF ablation should be aware that complication and success rates may differ from those reported by selected high-volume centres.